2013
DOI: 10.1177/0269216313477178
|View full text |Cite
|
Sign up to set email alerts
|

Bereaved relatives’ perspectives of the patient’s oral intake towards the end of life: A qualitative study

Abstract: This study revealed the complexity of meaning relatives' experiences with dying patients' decreasing oral intake. Their perceptions and concerns were related to their awareness of the imminent death. These findings can guide staff involved in care delivery to better support relatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 22 publications
0
44
0
3
Order By: Relevance
“…The discrepancy in the rating of severity of swallowing does suggest, however, a need for a better communication between relatives and nursing staff. Raijmakers et al [8] studied the relatives' perspective of the patient's oral intake toward the end of life in 23 patients and found that relatives recalled limited communication with health care professionals concerning oral intake at the end of life. The results of our study seem to support the findings by Raijmakers et al [8] and underline the need for providing adequate information on swallowing problems to the relatives when a patient receives palliative care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The discrepancy in the rating of severity of swallowing does suggest, however, a need for a better communication between relatives and nursing staff. Raijmakers et al [8] studied the relatives' perspective of the patient's oral intake toward the end of life in 23 patients and found that relatives recalled limited communication with health care professionals concerning oral intake at the end of life. The results of our study seem to support the findings by Raijmakers et al [8] and underline the need for providing adequate information on swallowing problems to the relatives when a patient receives palliative care.…”
Section: Discussionmentioning
confidence: 99%
“…Raijmakers et al [8] studied the relatives' perspective of the patient's oral intake toward the end of life in 23 patients and found that relatives recalled limited communication with health care professionals concerning oral intake at the end of life. The results of our study seem to support the findings by Raijmakers et al [8] and underline the need for providing adequate information on swallowing problems to the relatives when a patient receives palliative care. Our data suggest however that this information should not be limited to swallowing problems only, but also focus on the links between these problems and other clinical symptoms, like loss of appetite.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to relatives of palliative patients, it has been noted that oral intake towards the end of life holds a variety of meaningful traits ranging from nutritional value to social animation [23]. Equally variable, are caregiver's responses to the oral feeding of their palliative relative.…”
Section: Discussionmentioning
confidence: 99%
“…Equally variable, are caregiver's responses to the oral feeding of their palliative relative. Some view their relatives declining oral intake as a self-choice to be respected, while others feel the need to combat a declining oral intake as a method to delay death [23]. Thus, the views of the caregiver toward the feeding habits of their palliative elder, remain an important talking point during clinical encounters.…”
Section: Discussionmentioning
confidence: 99%